2016
DOI: 10.1080/1359432x.2016.1168402
|View full text |Cite
|
Sign up to set email alerts
|

Flexible job search behaviour among unemployed jobseekers: antecedents and outcomes

Abstract: The interest in flexible job search behaviour (FJSB) among unemployed jobseekers, i.e., the extent to which jobseekers also look for jobs that deviate from their studies and earlier work experience, has grown considerably in recent years. Yet, there is large disagreement on both its consequences and drivers. Career scholars as well as policymakers believe that FJSB is important for unemployed and can improve their employment prospects. However, evidence from HR literature raises doubts whether FJSB can enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 107 publications
(156 reference statements)
0
17
0
Order By: Relevance
“…Sample demographic characteristics are summarized in Table 1. Studies generally used correlational, crosssectional designs (90% of included samples), with a small number of studies employing experimental/intervention (1% of samples; Unite, 2014; Verbruggen & Sels, 2008) or longitudinal/predictive designs with follow-up periods ranging from 3-18 months (9% of samples; Dries, 2015;Fleisher, Khapova, & Jansen, 2014;Galais & Moser, 2009;Gubler et al, 2014a;Herrmann, 2013;Lo Presti, 2008;McArdle, Waters, Briscoe, & Hall, 2007;Ng & Feldman, 2015;Supeli & Creed, 2016;Vansteenkiste, Verbruggen, & Sels, 2016;Woo & Porter, 2017). Table 2 lists construct definitions and example scales.…”
Section: Meta-analytic Samplementioning
confidence: 99%
“…Sample demographic characteristics are summarized in Table 1. Studies generally used correlational, crosssectional designs (90% of included samples), with a small number of studies employing experimental/intervention (1% of samples; Unite, 2014; Verbruggen & Sels, 2008) or longitudinal/predictive designs with follow-up periods ranging from 3-18 months (9% of samples; Dries, 2015;Fleisher, Khapova, & Jansen, 2014;Galais & Moser, 2009;Gubler et al, 2014a;Herrmann, 2013;Lo Presti, 2008;McArdle, Waters, Briscoe, & Hall, 2007;Ng & Feldman, 2015;Supeli & Creed, 2016;Vansteenkiste, Verbruggen, & Sels, 2016;Woo & Porter, 2017). Table 2 lists construct definitions and example scales.…”
Section: Meta-analytic Samplementioning
confidence: 99%
“…Numerous studies have shown that unemployment adversely affects the psychological and physical wellbeing of people (McKee-Ryan et al, 2005 ; Mousteri et al, 2018 ; Paul & Moser, 2009 ) and is particularly devastating for unemployed young adults (Mokona et al, 2020 ; Thern et al, 2017 ). Most of the job search literature has focused on job search behavior of the individual (see Hoye et al, 2015 ; Vansteenkiste et al, 2016 ). However, much less research has been aimed at understanding the social support system that is available to the young adult job seeker.…”
Section: Introductionmentioning
confidence: 99%
“…Both employed and unemployed workers combine different channels and methods of job searching [48,50,54,55,58,59], although the most educated people, who have higher levels of training and professional qualifications, use a greater number of strategies simultaneously and use predominantly formal methods over informal methods [58]. The Internet stands out as a job-search tool [41,50,53,54,59–64] because it succeeds in smoothing markets and eliminating physical and geographic barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the study aims to answer the following research question: what differences exist among job-search behaviours developed by individuals at different levels of risk of poverty and social exclusion? Based on previous empirical evidence [37,43,45,52,55,56,58], the starting hypothesis is that people at high risk of social exclusion make use, to a greater extent than people with low risk, of informal strategies that require a low level of job-search skills. Identifying the strategies to which lesser-experienced individuals resort is relevant information for the services and other entities that endeavour to assist this group.…”
Section: Introductionmentioning
confidence: 99%